PTU-131 Cardiopulmonary exercise testing predicts prolonged hospital stay following oesophago-gastric cancer surgery. (22nd June 2015) - Tan, B; Sylvester, K; Rashid, F; Sujendran, V; Hindmarsh, A; Safranek, P; Hardwick, R
Abstract : Introduction: Preoperative cardiopulmonary exercise testing (CPEX) has been shown to be useful in assessing operative risks in patients undergoing major surgery. The aim of this study was to assess the value of CPEX in predicting complications and prolonged hospital stay in patients undergoing oesophago-gastric cancer resection. Method: Between November 2013 and November 2014, 68 patients (52 men, 16 women) with a median age of 67 (range 32–82) years underwent CPEX before potentially curative resections for oesophago-gastric cancer. CPEX variables measured included oxygen uptake at the estimated lactate threshold (AT) and at peak exercise (VO2 max). Patients were mobilised on the first postoperative day with epidural analgesia and all oesophagectomy patients had feeding jejunostomies with feed starting on postoperative day one. Postoperative morbidity and mortality was determined using the Clavien-Dindo classification. Results: The mean AT was 12.6 ± 3.1 ml kg -1 min -1 (mean ± SD) and the mean VO2 max was 20.5 ± 5.5 ml kg -1 min -1 . Serious post-operative complications (Clavien-Dindo score ≥3) occurred in 18 (26.5%) patients. There was no significant association between all variables of CPEX and the development of post-operative complications. Median length of hospital stay was 11 (range 6–78) days. VO2 max and body mass index (BMI) was associated with increased length of hospital stay (weight coefficient: -0.271; 95% C. I: -1.049 – -0.071; p = 0.025 and weight coefficient: 0.259; 95% C. I: 0.045–1.054; p = 0.033 respectively) on univariate linear regression analysis. Only VO2 max retained independent association with length of hospital stay on multivariate analysis. Conclusion: CPEX is a poor predictor of post-operative complications in patients undergoing curative oesophago-gastric cancer resection. However, a lower VO2 max may be useful in identifying patients 'at risk' of prolonged length of hospital stay. Disclosure of interest: None Declared.